2013
DOI: 10.1007/s13197-013-1119-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the nutraceuticals composition of wheat derived oils wheat bran oil and wheat germ oil

Abstract: Fat-soluble nutraceuticals of cereals are known for number of disease preventive activities. Hence wheat bran oil (WBO) and wheat germ oil (WGO) were extracted from wheat bran and germ which yielded 3.35 % and 7.35 % of oil, containing polyunsaturated fatty acids (PUFA) (64 %, 61.2 %) respectively. Both oils contained tocopherols and carotenoids, which were higher in wheat germ oil (273 mg/ 100 g, 12.23 mg/100 g) than wheat bran oil (190 mg/100 g, 2.21 mg/100 g). Steryl ferulates were also present in both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 22 publications
(17 reference statements)
8
48
2
1
Order By: Relevance
“…In another study, rye bran and wheat bran steryl ferulates were compared and yields obtained were different (Nyström et al 2007). Suresh Kumar and Gopala Krishna (2015) and Suresh Kumar et al (2014) have also reported the changes in wheat bran oil steryl ferulates before and after heating at different temperatures. Steryl ferulates has significant effects in reducing serum cholesterol levels, inhibiting tumorigenesis, anti-diabetic properties etc.…”
Section: Steryl Ferulate Content Of Wheat Bran Varietiesmentioning
confidence: 97%
“…In another study, rye bran and wheat bran steryl ferulates were compared and yields obtained were different (Nyström et al 2007). Suresh Kumar and Gopala Krishna (2015) and Suresh Kumar et al (2014) have also reported the changes in wheat bran oil steryl ferulates before and after heating at different temperatures. Steryl ferulates has significant effects in reducing serum cholesterol levels, inhibiting tumorigenesis, anti-diabetic properties etc.…”
Section: Steryl Ferulate Content Of Wheat Bran Varietiesmentioning
confidence: 97%
“…Mixed tocopherols from soybean oil processing are generally used for stabilizing oxidatively-sensitive lipid supplements such as those from marine oils and other products. In addition, tocopherol-rich oils, such as germ oils from oat [63], barley [64] and wheat [65], may be mixed with other oils to stabilize them [61]. Among the tocotrienol-rich oils, palm oil [28], annatto [66], and rice bran oil [67] are important, and these are often used in product enrichment.…”
Section: Current and Potential Applications Of Tocopherols And Tocmentioning
confidence: 99%
“…In a recent study, Kumar and Krishna (2013) used HPLC and NMR ( 13 C and 1 H) to determine the distribution of tocopherols and carotenoids in the unsaponifiable matter of wheat bran and wheat germ oils. These results showed that wheat germ oil contained higher concentrations of tocopherols and carotenoids (273 and 12.23 mg/100 g, respectively) than wheat bran oil (190 and 2.21 mg/100 g, respectively).…”
Section: Analysis Of Carotenoids and Tocopherolsmentioning
confidence: 99%